Clearing the JUNQ: the molecular machinery for sequestration, localization, and degradation of the JUNQ compartment - Rolli, Sarah; Langridge, Chloe A.; Sontag, Emily M. (Frontiers in Molecular Biosciences, 2024)
Cellular protein homeostasis (proteostasis) plays an essential role in regulating the folding, sequestration, and turnover of misfolded proteins via a network of chaperones and clearance factors. Previous work has shown that misfolded proteins are spatially sequestered into membrane-less compartments in the cell as part of the proteostasis process. Soluble misfolded proteins in the cytoplasm are trafficked into the juxtanuclear quality control compartment (JUNQ), and nuclear proteins are sequestered into the intranuclear quality control compartment (INQ). However, the mechanisms that control the formation, localization, and degradation of these compartments are unknown. Previously, we showed that the JUNQ migrates to the nuclear membrane adjacent to the INQ at nucleus-vacuole junctions (NVJ), and the INQ moves through the NVJ into the vacuole for clearance in an ESCRT-mediated process. Here we have investigated what mechanisms are involved in the formation, migration, and clearance of the JUNQ. We find Hsp70s Ssa1 and Ssa2 are required for JUNQ localization to the NVJ and degradation of cytoplasmic misfolded proteins. We also confirm that sequestrases Btn2 and Hsp42 sort misfolded proteins to the JUNQ or IPOD, respectively. Interestingly, proteins required for piecemeal microautophagy of the nucleus (PMN) (i.e., Nvj1, Vac8, Atg1, and Atg8) drive the formation and clearance of the JUNQ. This suggests that the JUNQ migrates to the NVJ to be cleared via microautophagy.